Delaying the timing of offshoring low-skilled tasks - de Mello-Sampayo, F.; de Sousa-Vale, S.; Camões, F. (Economic Modelling, 2010)
This paper examines the impact of uncertainty on offshoring low-skilled tasks. The model shows that greater demand uncertainty adversely affects the expected profit and timing of offshoring. It is also shown that a home-country tax rate deduction increases the volatility of the expected profits, making offshoring appear to be more risky. One policy implication of our results is that, in order to delay relocation of MNE's production from the home country, a government should adopt tax rate deduction rather than a direct subsidy because the former is more economical and effective than the latter.